2012
DOI: 10.1186/1471-2334-12-78
|View full text |Cite
|
Sign up to set email alerts
|

Improving resolution of public health surveillance for human Salmonella entericaserovar Typhimurium infection: 3 years of prospective multiple-locus variable-number tandem-repeat analysis (MLVA)

Abstract: Background Prospective typing of Salmonella enterica serovar Typhimurium (STM) by multiple-locus variable-number tandem-repeat analysis (MLVA) can assist in identifying clusters of STM cases that might otherwise have gone unrecognised, as well as sources of sporadic and outbreak cases. This paper describes the dynamics of human STM infection in a prospective study of STM MLVA typing for public health surveillance. Methods During a three-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…All the serial S. Typhimurium isolates from the same patient were grouped together. Isolates from patients 4, 6, 8, and 10 clustered together, and based on their relationship with the DT170 isolates, it is likely that they belonged to phage type DT170, the most common phage type in NSW, Australia, where the patients resided (7). The phylogenetic analysis showed that the isolates from carriers did not belong to a single clone.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…All the serial S. Typhimurium isolates from the same patient were grouped together. Isolates from patients 4, 6, 8, and 10 clustered together, and based on their relationship with the DT170 isolates, it is likely that they belonged to phage type DT170, the most common phage type in NSW, Australia, where the patients resided (7). The phylogenetic analysis showed that the isolates from carriers did not belong to a single clone.…”
Section: Resultsmentioning
confidence: 97%
“…In the state of New South Wales (NSW), the notification rate has been around 50 cases per 100,000 population (5). Sequencing of S. Typhimurium genomes or analyses of tandem repeats within the genome have increasingly been employed for tracking community outbreaks and transmission chains (6,7). However, the magnitude of genomic variation in isolates associated with carriage remains unknown.…”
mentioning
confidence: 99%
“…Multilocus sequence typing (MLST) has a low resolution to type S. Typhimurium, as the majority of isolates belong to sequence type 19 (ST19) (10). Multilocus variable-number tandem-repeat analysis (MLVA) has been adopted as a standardized method in Australia (9,11) and Europe (12). However, the numerical dominance of endemic MLVA types reduces the power of MLVA for outbreak investigations.…”
mentioning
confidence: 99%
“…Therefore, phage typing has limited resolution for outbreak detection. More recently, multilocus variable-number tandem-repeat (VNTR) analysis (MLVA) has been adopted in public health reference laboratories across Australia for epidemiological typing because of its relatively high discriminatory power and ability to be harmonized (1). MLVA has also been used as a standardized method for outbreak detection in Europe (2,3).…”
mentioning
confidence: 99%
“…In New South Wales (NSW), Australia, all Salmonella isolates from public and private pathology providers are routinely referred to the NSW Enteric Reference Laboratory, Institute for Clinical Pathology and Medical Research (ICPMR), Westmead Hospital, for serotyping and MLVA typing using five VNTR loci (MLVA-5) (1). Prospective MLVA typing of S. Typhimurium has been useful for identifying outbreak clusters (1).…”
mentioning
confidence: 99%